Civil service reform in Ethiopia: Issues, lessons and future directions - Markos, Solomon (2013)
This article provides an in-depth review of the successes and challenges of public sector reform efforts in Ethiopia with a view to help other developing countries, particularly African countries, learn from Ethiopia's experiences in this regard so that they can improve the content of and approach to their public sector reforms. It also identifies the gaps in the existing literature and puts forward implications for further research in the area. The public sector reform program of Ethiopia has shown successes particularly in the areas of service delivery to citizens. However, the reform program is entangled with challenges such as lack of accountability and transparency on the part of implementing institutions,inadequate material and moral incentive to employees thus crippling the capacity to manage the implementation process, and participation from the side of different stakeholders. - Reproduced.
Keywords: Civil service - Ethiopia; Administrative reform - Ethiopia; Administrative reform